Serum expression of ESM-1 and Syndecan-1 and its relationship with disease severity in children with Mycoplasma pneumoniae pneumonia - Yanjuan Yu; Yanyan Su; Xiuhong Jin; Xiangfeng Zhang; Yeran Yang; Yuelin Shen (Italian Journal of Pediatrics)
Abstract Background This study aim to investigate the role of endothelial damage in the pathogenesis of Mycoplasma pneumoniae pneumonia (MPP) by comparing serum levels of endothelial cell-specific molecule 1 (ESM-1) and Syndecan-1 in patients with varying degrees of MPP severity. Additionally, we aim to explore the relationship between the production of ESM-1 and Syndecan-1 and the severity of MPP, inflammation, as well as hypercoagulative state in children. Methods A prospective, observational study that included clinical manifestations, laboratory tests, and serum ESM-1 and Syndecan-1 assays. The correlation between ESM-1 and Syndecan-1 levels with inflammatory markers and coagulation markers was analyzed. Multivariate logistic regression analysis was conducted to identify significant risk factors for Severe Mycoplasma pneumoniae pneumonia (SMPP). Results A total of 179 children with MPP and 40 healthy volunteers were enrolled. Serum ESM-1 and Syndecan-1 levels were significantly elevated in children with MPP compared to the healthy children (all P < 0.05). A multivariate analysis revealed that ESM-1, Syndecan-1, D-dimer and LDH were the significant predictors of SMPP, with odds ratios of 1.034, 1.002, 5.042 and 1.014, respectively. The optimal cutoff values of ESM-1, Syndecan-1, D-dimer and LDH for predicting SMPP were 79.67 ng/mL, 3219.35 pg/mL, 0.67 µg/mL and 365.00 U/L, respectively. Conclusions ESM-1, Syndecan-1, D-dimer, and LDH can serve as independent predictors for SMPP. The interaction between endothelial damage, excessive inflammatory response, and hypercoagulable state collectively contributes to the development and progression of SMPP.